Optical frequency combs for optical fiber communications - Leif Katsuo Oxenløwe (APL Photonics)
Optical frequency combs are analyzed in the context of using them for carrying data in optical fiber communication systems. Combs are analyzed for their data-carrying capacity, i.e., for how much data they can carry, in massively multiplexed systems, and for their transmission reach capabilities, i.e., for how long cables they would be useful sources. The challenge is their limited output power and, hence, the need for amplification, which limits the initial signal-to-noise ratio and, hence, the data capacity they can support. It is shown that currently, available comb sources can individually support multiple Pbit/s in short multiplexed links and also support ultra-long-haul reach with performance on par with using high-quality individual lasers. This means that, provided a number of practical solutions for matching and tuning combs, as well as replacing broken comb sources swiftly, are developed, amplified optical frequency combs could perform very well as replacements for banks of individual lasers in optical networks.